Persiapan Akreditasi Sekolah Melalui Diseminasi - Nila Lukmatus Syahidah (Journal of Islamic Education Management, 2022)
This study aims to provide an overview to schools that are the target of accreditation visitations to carry out preparations for accreditation, especially the delivery of information obtained related to the many changes in paradigm, implementation, and ranking of accreditation. Target schools often receive information regarding their determination as target schools for accreditation in a short time, so preparation for accreditation must be carried out jointly and supported by understanding from all schools involved in accreditation. This research was conducted using a qualitative approach. Researchers collect data through observation and interviews. Furthermore, the data is reduced, presented, and concluded. Schools choose dissemination as an effort to start preparations for accreditation. By conducting dissemination, information related to changes and the implementation of accreditation can spread quickly and to many parties, so that every school party involved in preparing for accreditation obtains clear and directed information. And each party can follow up according to the task of preparation for accreditation that has been given to them. Key word: School accreditation preparation, Dissemination.